2022
DOI: 10.1371/journal.pone.0273797
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of phosphohistidine in proteins in a mammalian cell line by 31P NMR

Abstract: There is growing evidence to suggest that phosphohistidines are present at significant levels in mammalian cells and play a part in regulating cellular activity, in particular signaling pathways related to cancer. Because of the chemical instability of phosphohistidine at neutral or acid pH, it remains unclear how much phosphohistidine is present in cells. Here we describe a protocol for extracting proteins from mammalian cells in a way that avoids loss of covalent phosphates from proteins, and use it to measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…The signals 8.15 ppm and −0.90 arise from an unknown impurity present in potassium phosphoramidate that was carried forward. The respective chemical shift values of τ‐pHis and π‐pHis do not change significantly between pH 10‐ 12 [11,30] …”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…The signals 8.15 ppm and −0.90 arise from an unknown impurity present in potassium phosphoramidate that was carried forward. The respective chemical shift values of τ‐pHis and π‐pHis do not change significantly between pH 10‐ 12 [11,30] …”
Section: Resultsmentioning
confidence: 92%
“…The respective chemical shift values of τ-pHis and π-pHis do not change significantly between pH 10-12. [11,30] combination of alanine glycine peptides containing triazolyl side chains 6 were used (Figure 5). [18] In the report which described the generation of τ-pHis (SC56-2) and π-pHis (SC1-1, SC50-3) monoclonal antibodies, the selectivity of these anti-bodies were assessed by dot blot/western blots of peptides containing pTyr side chain 2, triazolyl side chains 3 and 6, and in vitro phosphorylated NME1/NME2 and PGAM1 but not ELISA.…”
Section: Synthesis Of τ-Phis and π-Phis Antibody Binders; Bsa-g-τ-phi...mentioning
confidence: 99%
See 2 more Smart Citations
“…Having demonstrated that 13H peptide is sufficient to undergo iH-PPn, we used this peptide for NMR studies. Phosphohistidine (pHis) is known to exhibit a characteristic P-N phosphoramidate bond peak in 31 P NMR at approximately -5 ppm, 31,32 which we would expect to observe if polyP attachment to histidine was covalent as it is presumed to be for K-PPn. A clear phosphoramidate peak at -5 ppm is visible for the pHis positive control, 33 but the 13H peptide treated with polyP displays no such peak (Figure 3D).…”
Section: Histidine Repeat Alone Is Sufficient For Ih-ppnmentioning
confidence: 95%